Total Pancreatectomy for Ampullary Adenocarcinoma in a 74-Year-Old Patient: Case Report and Literature Review - Gabriela A. Arroyo Murillo; Eleonore Choppin De Janvry; Manuela Garofalo; Fatima Della Pietra (Case Reports in Surgery)
Primary ampullary neoplasms have origin in the ampulla of Vater, an anatomical structure where the common bile duct and the pancreatic duct join together as a common channel. It represents <0.5% of all gastrointestinal cancers and approximately 7% of all periampullary cancers. The adenocarcinomas arising in this region originate from different epithelial cellular constituents present at the site, the histopathological classification encompass: intestinal type, pancreaticobiliary type, and mixed type. Pancreaticoduodenectomy is the treatment of choice when there is an overt or highly suspicious malignant behaviour. We present here the case of a 74-year-old male patient who presented to our department for further investigation of obstructive jaundice and a pancreatic mass associated with a six-month history of significant weight loss and mild epigastric pain. Eventually, a total splenopancreatectomy was performed given the extension of structural anomalies of the organ secondary to an ampullary adenocarcinoma.